THE INFLUENCE OF STATING METHODS ON DHILDREN”S LAGUAGE DEVELOPMENT IN GROUP B2 ADHYAKSA TK XXII PALU - Nur Rahma (Universitas Tadulako, 2020)
The problem in this study is that children's language development has not developed as expected. The aim is to determine the effect of storytelling methods on children's language development. The research method used is a quantitative approach and experimental research types. The subjects of this study were 21 children in Group B2 TK Adhyaksa XXII Palu. Data collection techniques are carried out through observation, interviews, and documentation. Data processing was done by using percentage techniques and t test (paired sample t-test). Data from the recapitulation of observations of children's language development before being given treatment in the form of a storytelling method, in the three observed aspects, there were 0% in the BSB category, 12.70% in the BSH category, 52.38% in the MB category, and 34.92% in the BB category. After being given treatment in the form of a storytelling method, from the results of the recapitulation of observations of children's language development in the three observed aspects, it was obtained an average of 55.55% in the BSB category, 22.22% in the BSH category, 22.23% in the MB category, and 0% in the BB category. Based on the results of the t-test calculation data, it is obtained that the value of tug> t table (20.088> 1.724), and a significant value of 0.000 <0.05. it can be concluded that Ho is rejected and H1 is accepted, which means there is an influence of the storytelling method on children's language development in Group B2 TK Adhyaksa XXII Palu.